The Effect of Motivation, Work Experience and Competence on Employee Performance of CV Global Health Science Group - Herli Rita Devi; Andi Kartika (Indonesian Journal of Global Health Research, 2026)
This study aims to analyze the influence of motivation, work experience, and competence on employee performance at CV Global Health Science Group. Employee performance is an important factor in achieving company goals, so it needs to be supported by high work motivation, adequate work experience, and competencies appropriate to the field of work. The research method used is a quantitative method with a survey approach. Data were collected by distributing questionnaires to CV Global Health Science Group employees as research respondents. The data analysis technique used multiple linear regression analysis to determine the effect of each independent variable on the dependent variable. The results of the study indicate that motivation, work experience, and competence have a positive and significant effect on employee performance, both partially and simultaneously. Thus, it can be concluded that increasing work motivation, developing work experience, and improving employee competence can improve employee performance optimally.